COMPARATION OF DISTRIBUTED DATABASE MODEL BY CLUSTERING METHOD IN E-GOVERNMENT SYSTEM. STUDY AT KEMENKEU RI - Adinda Krida Wicaksono; Fauzie Nurrakhman; Samidi Samidi (Informatika, Universitas Jenderal Soedirman, 2023)
MySQL is one of the most popular open source database in the world based on its performance, its reliability, and its easiness that has been proved. MySQL is categorized into community version and commercial version. The commercial version has standalone architecture models and clusters.Database Clustering is one of distributed database model. The case study used is Kemenkeu Learning Center (KLC) Application which is an e-government application in Ministry of Finance. KLC application used for interactive learning media for all ASN especially ASN in Ministry of Finance. This makes the KLC application being categorized into a very high critical application, so it takes a good response time and has high availability. One of the most important factors to fulfill this need is by deciding the appropriate MySQL database architecture for KLC application. This research was conducted by creating 3 (three) database architecture models according to best practice from MySQL, namely the Standalone architecture model, InnoDB Cluster and NDB Cluster. Then tested with several different scenarios to get results in the form of response time and percentage of errors that indicate high availability capabilities. The tools used in testing are Apache JMeter. From the test results, it is found that the MySQL NDB Cluster is the right database architecture model in an effort to realize the need for database services with the best response time and high availability capabilities.